2022
DOI: 10.3389/fendo.2022.818388
|View full text |Cite
|
Sign up to set email alerts
|

In Obese Patients With Type 2 Diabetes, Mast Cells in Omental Adipose Tissue Decrease the Surface Expression of CD45, CD117, CD203c, and FcϵRI

Abstract: The paradigm of mast cells in type 2 diabetes is changing. Although they were first considered deleterious inflammatory cells, now they seem to be important players driving adipose tissue homeostasis. Here we have employed a flow cytometry-based approach for measuring the surface expression of 4 proteins (CD45, CD117, CD203c, and FcϵRI) on mast cells of omental (o-WAT) and subcutaneous white adipose tissue (s-WAT) in a cohort of 96 patients with morbid obesity. The cohort was split into three groups: non-T2D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In recent years, many studies have reported that CD45 had promoted the development of diabetes and its metabolic syndrome. Studies have confirmed that the expression of PTPRC was related to β-cell function in DM, which directly influenced insulin secretion and glycemic control ( 23 ). Our results indicated that a higher expression of PTPRC was closely related to DN.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, many studies have reported that CD45 had promoted the development of diabetes and its metabolic syndrome. Studies have confirmed that the expression of PTPRC was related to β-cell function in DM, which directly influenced insulin secretion and glycemic control ( 23 ). Our results indicated that a higher expression of PTPRC was closely related to DN.…”
Section: Discussionmentioning
confidence: 94%
“…Obesity increases the infiltration of neutrophils and reduces the number of resident mast cells ( 9 , 10 ). Furthermore, obesity induces a pro-inflammatory phenotypic switching in macrophages and disrupts the function of mast cells ( 11 , 29 ). This state of low-level chronic inflammation, together with other factors (such as adipocyte hypertrophy, fibrosis, or tissue hypoxia) impairs the normal function of adipose tissue, promoting obesity-associated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic density was performed following the protocol developed by Lopez-Perez et al. ( 34 ). Briefly, the cells were washed with PBS and incubated with 2 µL of BV421 Mouse Anti-Human Alkaline Phosphatase (BD Biosciences) for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%